IMPLEMENTASI P5 TEMA “HIJAUNYA SEKOLAH” PADA SDN MARGOREJO 1/403 SURABAYA - Siti Nur Halimah; Susilawati; Vina Siti Alifah; Siti Haifa; Mar’atul Khasanah; Muhammad Nurfaisal Sidik (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Implementation of the Pancasila Student Profile Strengthening Project (P5) is a program that aims to shape the character of students in accordance with Pancasila values. One of the implementations of P5 at SDN Margorejo 1 Surabaya City is through the theme "Green Schools." The aim of this research is to increase students' environmental awareness by creating a green, clean and beautiful school environment. Activities carried out include planting trees, caring for plants in the school garden, and using empty land for hydroponic plants. Apart from that, students are also given education about the importance of maintaining environmental cleanliness and sustainability through discussions, presentations and direct practice activities. Data collection was done through direct observation and interviews with descriptive qualitative research. The method used in implementing this program is a project-based approach (P5), where students play an active role in planning and evaluation activities. The results of this implementation show an increase in student awareness and participation in protecting the school environment. Apart from that, the school environment becomes greener and more comfortable. This program not only has an impact on school aesthetics, but also instills the values of mutual cooperation, responsibility and concern for the environment. Thus, the implementation of the "Green Schools" theme at SDN Margorejo 1/403 Surabaya can be an example for other schools in implementing character-based education and environmental sustainability.Keywords: P5, Green School, Environment, Character, SDN Margorejo 1. Pelaksanaan Projek Penguatan Profil Pelajar Pancasila (P5) merupakan program yang bertujuan untuk membentuk karakter peserta didik sesuai dengan nilai-nilai Pancasila. Salah satu implementasi P5 di SDN Margorejo 1 Kota Surabaya adalah melalui tema “Hijaunya Sekolah.” Tujuan Penelitian ini bertujuan untuk meningkatkan kesadaran lingkungan siswa dengan menciptakan lingkungan sekolah yang hijau, bersih, dan asri. Kegiatan yang dilakukan meliputi penanaman pohon, perawatan tanaman di taman sekolah, serta pemanfaatan lahan kosong untuk tanaman hidroponik. Selain itu, siswa juga diberikan edukasi mengenai pentingnya menjaga kebersihan dan keberlanjutan lingkungan melalui kegiatan diskusi, presentasi, dan praktik langsung. Pengambilan data melalui observasi dan wawancara secara langsung dengan penelitian kualitatif deskriptif. Metode yang digunakan dalam implementasi program ini adalah pendekatan berbasis proyek(P5), di mana siswa berperan aktif pada kegiatan perencanaan hingga evaluasi.Hasil dari implementasi ini menunjukkan adanya peningkatan kesadaran dan partisipasi siswa dalam menjaga lingkungan sekolah. Selain itu, lingkungan sekolah menjadi lebih hijau dan nyaman. Program ini tidak hanya berdampak pada estetika sekolah, tetapi juga menanamkan nilai-nilai gotong royong, tanggung jawab, dan kepedulian terhadap lingkungan. Dengan demikian, implementasi tema “Hijaunya Sekolah” di SDN Margorejo 1/403 Surabaya dapat menjadi contoh bagi sekolah lain dalam mengimplementasikan pendidikan berbasis karakter dan keberlanjutan lingkungan.Kata Kunci: P5, Hijaunya Sekolah, Lingkungan, Karakter, SDN Margorejo 1.